Six weeks of intensive rehearsals for the Swan Lake ballet shows ultrasound tissue characterization changes of the Achilles tendons in dancers - Anker-Petersen, C.; Juul-Kristensen, B.; Antflick, J.; Aagaard, H.; Myers, C.; Ploug Boesen, A.; Boyle, E.; Hölmich, P.; Thorborg, K. (Scandinavian Journal of Medicine & Science in Sports, 2021)
The objective was to investigate, first, whether six weeks of intensive ballet dance exposure is associated with structural and clinical changes in the Achilles tendon; second, the importance of demographics, self-reported Achilles pain, and generalized joint hypermobility (GJH). Data were collected at baseline and at six weeks` follow-up, using Achilles tendon ultrasound tissue characteristics (UTC) as primary outcome (percentage distribution of echo-type I-IV: type I = intact and aligned bundles, type II = discontinuous/wavy bundles, type III = fibrillar, and type IV = amorphous cells/fluid). Secondary outcomes included clinical signs of Achilles tendinopathy, Achilles tendon pain during single-leg heel raise, self-reported symptoms (VISA-A questionnaire), and GJH. Sixty-three ballet dancers (aged 18-41) participated. From baseline to follow-up, UTC echo-type I decreased significantly (ß = -3.6, p = 0.001; 95% CI: -5.8;-1.4), whereas echo-type II increased significantly (ß = 3.2, p < 0.0001, 95% CI: 1.6;4.8). Furthermore, a significant effect of limb (left limb showed decreased echo-type I and increased echo-type III + IV) and sex (women showed decreased echo-type I and increased in type II) was found. No significant changes in the remaining secondary outcomes were found. Ballet dancers showed structural changes in UTC, corresponding to a decreased echo-type I distribution after six weeks of rehearsing for Swan Lake ballet. No changes in self-reported symptoms, clinical signs of Achilles tendinopathy, and single-leg heel raise test were seen from pre- to post-rehearsal. Thus, UTC changes in the Achilles tendon seem to appear earlier than clinical signs of tendinopathy.